Prinsip Kehati-Hatian Bank Dalam Mencairkan Dana Nasabah Yang Telah Meninggal Dunia (Studi Putusan Mahkamah Agung Nomor 1050 K/Pdt/2015) - Hendra Adiwijaya; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Medan Area, 2022)
This study aims to find out how the application of the prudential banking principle is included in disbursing the funds of customers who have died. The Supreme Court's decision Number 1050 K/Pdt/2015 is a decision from a civil dispute over a lawsuit against the law from several legal heirs because the customer's funds have been disbursed to a third party who is not the heir of the deceased customer. The research method used in this research is normative research that uses a statutory approach, a conceptual approach, and a case approach. The data collection used in this research is library research, which is then analyzed qualitatively and conclusions are drawn using the deductive method. The results of the study explain that the Bank applies the precautionary principle in disbursing funds from customers who have died based on the Standard Operating Procedures (SOP) of the bank. The responsibility of the bank for failure to apply the prudential principle of the bank in disbursing the funds of a deceased customer, namely by compensating or returning the funds that have been sought to third parties who are not his heirs to the real heirs based on evidence that the attached documents are in accordance with the regulations. legislation